The Route and Bus Stop Plan for Urban Agglomeration Transportation on the Educational Facility in Yogyakarta Urbanized Area - Syifa Hapsari Khaerunnisa; Siti Malkhamah; Latif Budi Suparma (Journal of the Civil Engineering Forum, 2021)
Public transportation is important in an urban area to provide better mobility and access to several destinations within the city. Therefore, this research was conducted to improve the Trans Jogja service as an Urban Agglomeration Transportation which is considered appropriate for residents, especially students, to ensure they shift to public transportation. The focus of this study was to develop the plan for the route and bus stop distribution in the educational facility covering high schools and universities in Yogyakarta Urbanized Area (YUA). The bus route network plan was formulated based on the number of student trips, land use, characteristics of the road network, route length, and travel time using multi-criteria analysis while the spatial analytical method was applied to cover the bus stop accessibility to schools and universities through two scenarios. The first was approximately a 200-meters radius while the second scenario was a 500-meters radius of accessibility and the route analysis showed the possibility of having 31 new routes of Yogyakarta Urban Agglomeration Transportation to cover the whole sub-districts in YUA including the Godean and Ngemplak which was not previously served by the Trans Jogja. The new routes consist of three outer city routes (OCR), 23 inner-city routes (ICR), and 5 connecting routes for the suburban and urban areas. Meanwhile, the bus stop was planned to focus on the new route as well as residential land use in a sub-urban area, high schools, and universities and the first scenario with a 200-meter radius has 99 units of the additional bus stop while the second with 500 meters has 66 units. This means the second scenario is better due to its coverage of a larger catchment area and other advantages and both the route network and bus stop addition plan were observed to have the equity concept to increase connectivity and accessibility for students.